Kesadaran Toleransi Sesuai Dengan Nilai Nilai Pancasila Di Kalangan Mahasiswa Gizi - Nurul Isnayni Salsabila; Fhilfa Nabilla Tasya; Yuli Salwa; Nova Amelia Putri; Zivana Hafiza Reysa (International Forum of Researchers and Lecturers, 2023)
As a country with a lot of diversity, Indonesia has a number of problems related to diversity. One effort to overcome this diversity conflict can be resolved with one thing, namely an awareness of tolerance. One form of problem that often arises is the issue of religious differences. This also happens among students majoring in nutrition. Therefore, there needs to be further discussion regarding the awareness of tolerance in accordance with the values contained in Pancasila. Activities to increase awareness of Pancasila values to form a tolerant attitude in nutrition students are carried out not only in Pancasila education courses but are carried out continuously and continuously every semester with the hope that every academic is required to implement them. The impact of implementing Pancasila values in students majoring in nutrition as an effort to realize an attitude of tolerance has a positive impact, namely increasing the feeling and attitude of caring for friends and neighbors who need it, creating an attitude of togetherness in every action that can be seen in places such as discussion groups, places. worship, organizational places, classrooms and others where students mix with each other and do not differentiate between religion, ethnicity, language